ITINERA LOQUUNTUR. LOS CONTENIDOS HISTÓRICOS DE LOS ANTIGUOS CAMINOS - López Caballero, Antonio C. (Antigüedad y Cristianismo, 1995)
The roads, one of the first and most transcendental activities which man carries out on his surroundings, often are an authentic historical document which provides valuable information on a variety of aspects: political, social, economical, ideologic al... The object of this paper is to make Known some of the keys to obtain such information.